The Government's Role in Handling People Smuggling in East Nusa Tenggara Province - Kiwang, Amir Syarifudin; Arifin, Amri Adha; Handayani, Suci Lestari; M Arif, Farida (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
People smuggling is an illegal practice that involves the smuggling of individuals or groups of people from one country to another with the aim of facilitating their unlawful presence. This research aims to identify the factors causing the occurrence of people smuggling in East Nusa Tenggara Province and the role of the government in addressing people smuggling in East Nusa Tenggara Province. This research uses a qualitative research approach.The data collection techniques are observation, interviews (interview guide), and documentation. For the sample in this study, purposive sampling was used. Then, the data validity testing includes credibility testing, transferability testing, reliability testing, and objectivity testing. The data analysis techniques, according to Miles and Huberman, use data reduction, data display, and conclusion or verification. The research results show that prolonged conflicts in the immigrants' countries of origin related to politics and security (such as Afghanistan, Bangladesh, Pakistan, etc.) as well as the poor economic conditions resulting from these conflicts drive the desire for a better life, becoming the main factors that give rise to the issue of people smuggling. The government's steps to anticipate and address the crime of people smuggling are through cooperation and collaboration from all related elements such as local governments, the military, the police, immigration, and UNHCR through socialization and guidance, joint sea patrols, and checking the legal status of foreigners and refugees.